FACTORS IMPACTING FINANCIAL LITERACY OF FARMERS IN KALABURAGI, KARNATAKA - C. HIREMATH (The Journal of Research ANGRAU, 2024)
The empirical study was conducted in 2023 in Kalaburagi, Karnataka. This reseacrh evaluated farmers’ ‘’financial literacy’’ levels and their impact on financial management. The financial literacy of farmers was assessed through a standardized knowledge index. Financial literacy was measured according to the OECD Toolkit (Organization for Economic Co-operation and Development). In the study area, 29 percent of farmers were high financial literate, 32 percent were moderate, and 39 percent were low financial literate. The financial literacy of farmers needed to improve. It was noted that was significant, implying 67 percent of the variation. Moreover, the significant F ratio (18.52) indicated that thefarmers’ financial literacy was impacted by age, education, farm income, and bank accounts. Farmer’s financial literacy significantly affected crop insurance, investment, KCC, mobile banking, crop loans, and other agriculture loans. To reach the farmers, better coordination should be with financial literacy centers and banks.